The Mother Country: Tracing Intersections of Motherhood and the National Story in Recent Canadian Historiography - Anderson, Kim (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This is an historiography involving books that address motherhood in Canada, with a focus on how these works demonstrate tensions related to gender, sexuality, class, race and ethnicity in the formation of the nation. The author traces her argument through approximately twenty-five books that have been written over the last thirty years.